PENDAMPINGAN KELUARGA PENERIMA MANFAAT PROGRAM KELUARGA HARAPAN DALAM PEMBENTUKAN KELOMPOK USAHA BERSAMA (KUBE) DI KECAMATAN BENGKAYANG KABUPATEN BENGKAYANG KALIMANTAN BARAT - Sabinus Beni; Blasius Manggu; Yosua Damas Sadewo (KACANEGARA Jurnal Pengabdian pada Masyarakat, 2021)
Community service activities are carried out in Bani Amas Village, Bengkayang District, West Kalimantan with the aim of poor families receiving conditional assistance. Hopeful Family Program with the aim of this community partnership program is to provide training and assistance in the establishment of joint business groups (KUBE) families of beneficiaries of the Hope Family Program. (PKH) in Bengkayang Subdistrict continuously both in terms of the process of making proposals to the operation of KUBE. The phenomenon that occurs from the first time the activities are carried out until the end of the effective six-month mentoring activity, families of beneficiaries of the Hope Family Program (PKH) have not been able to move further to achieve independence as has been envisioned by the Ministry of Social Affairs by fostering a spirit of entrepreneurship through joint business groups (KUBE). The partner of the community partnership program is the formation of 11 (eleven) Joint Business Groups (KUBE) of the Bengkayang District Family Hope Program in Bengkayang Regency to assist in making KUBE assistance proposals ready to be submitted to the Ministry of Social Affairs through the Bengkayang Regency Social Service. The partnership method used is providing training in the form of lectures, tutorials and discussions as well as making business proposals.